A Systematic Review of Metabolic Heat in Sea Turtle Nests and Methods to Model Its Impact on Hatching Success - Gammon, Malindi; Fossette, Sabrina; McGrath, Gavan; Mitchell, Nicola (Frontiers in Ecology and Evolution, 2020)
JJust as organisms do not passively exist in their environment, developing sea turtle embryos affect their own incubation microclimate by producing metabolic heat and other waste products. This metabolic heat ultimately contributes to successful development, but it is unclear how it influences embryonic traits such as hatchling sex, and whether trends exist in the magnitude of metabolic heat produced by different species. In this systematic review, we document all empirical measurements of metabolic heat in sea turtle species, its impact on their development, and explore the methods used to predict nest temperature and how these methods account for metabolic heat. Overall we found metabolic heat increases throughout incubation in all seven species. Typically, the temperature at the center of an egg clutch peaked during the final third of incubation, and exceeded the adjacent sand temperature by 2.5°C. Metabolic heat was not influenced by species or clutch size (n = 16 studies), but this finding was likely influenced by inconsistency in the methods used to measure metabolic heat, and by localised differences in sand properties, such as moisture, albedo and thermal conductivity. The influence of metabolic heat on embryo sex determination and survival was dependent on the sand temperature surrounding the nest chamber, and had an appreciable affect only when it caused nest temperatures to exceed key thresholds for sex determination and survival. Correlative models describe relationships between empirical data to predict sand temperature, while mechanistic models are based on physical laws and do not require extrapolation when predicting novel situations, such as climate change. Methods for modelling nest temperature were either correlative (70% of publications) or mechanistic (30% of publications). Most correlative models (74%) accounted for metabolic heat when predicting nest temperatures, but no mechanistic models did – largely because they were developed for predicting primary sex ratios, which are widely believed to be unaffected by metabolic heat. Consequently, developing a generalisable mechanistic model that incorporates metabolic heat will be critical for predicting incubation success as the sand temperatures at sea turtle beaches increase due to anthropogenic climate change.